Do Treatment Effects of a Web-Based Cognitive Behavioral Therapy for Insomnia Intervention Differ for Users With and Without Pain Interference? A Secondary Data Analysis - Shaffer, Kelly M. (J Behav Med, 2019)
Cognitive-behavioral therapy for insomnia (CBT-I) shows treatment benefits among individuals with pain interference; however, effects of Internet-delivered CBT-I for this population are unknown. This secondary analysis used randomized clinical trial data from adults assigned to Internet-delivered CBT-I to compare changes in sleep by pre-intervention pain interference. Participants (N=151) completed the Insomnia Severity Index (ISI) and sleep diaries (sleep onset latency [SOL]; wake after sleep onset [WASO]) at baseline, post-assessment, six- and twelve-month follow-ups. Linear mixed-effects models showed no differences between pain interference groups (no, some, moderate/severe) for changes from baseline to any follow-up timepoint for ISI (p=.72) or WASO (p=.88). There was a small difference in SOL between those reporting some vs. no or moderate/severe pain interference (p=.04). Predominantly comparable and sustained treatment benefits for both those with and without pain interference suggest that Internet-delivered CBT-I is promising for delivering accessible care to individuals with comorbid pain and insomnia.